"From Sweats to Suits": Administrators’ Recommendations For Student-Athlete Career Development Services. - Sears, Jackson; Bunch, Natalie; Williams, Tyler; Cianfrone, Beth (Journal of Intercollegiate Sport, 2024)
Division I college athletes are faced with numerous academic challenges during their time in school, including conflicts of interest between the university (e.g., academic success), athletic department (e.g., athletic success), and their own priorities (e.g., quality of life, balancing academic and athletic success). These growing demands may impact student-athletes’ ability to prepare for a career after sport. Thus, there is a need for high-quality student-athlete career development programming and services in student-athlete support centers. The purpose of this study was to gain senior administrators’ perspectives of student-athlete support services to determine best practices of career development programming. Division I administrators (N = 10), who oversee student-athlete support centers, provided insight and feedback via semi-structured interviews. A directed qualitative content analysis was conducted to discern best practices, levels of student-athlete engagement, and preferred attributes of career development personnel. The findings provide specific recommendations, which can help other student-athlete career development personnel improve their programs and adds to the holistic care literature.